Germination of five weed species of Convolvulaceae family under the effect of temperature - Labonia, Victor Domiciano de Silos; Presoto, Jéssica Cursino; Andrade, Jeisiane de Fátima; Carvalho, Saul Jorge Pinto de; Victoria Filho, Ricardo (Revista Agrogeoambiental, 2019)
Seeds of several weed species have distinct development when germinating under different conditions of temperature, promoting variation on the management system. Thus, this work was carried out with the objective of evaluating the influence of temperature on the germination of five weed species of Convolvulaceae family, commonly known as morning glory. The work was performed in termogradient table and constituted by five independent experiments, divided by species, in a factorial combination of nine treatments (temperatures) and two seed dormancy breaking conditions (with or without acid scarification). The weed species were: Ipomoea triloba, I. hederifolia, I. quamoclit, I. nil and Merremia cissoides. Nine temperature intervals between 15 and 35ºC were evaluated, under 8 hours of daily photoperiod. Experimental design adopted was totally randomized with four replicates. Percentage of germination was evaluated daily; the speed of germination index was calculated for the species. Generally, it was evident that temperatures lower than 17,2 ºC reduced significantly germination of all species, inhibiting germination of I. quamoclit. Species demonstrated capacity of germinating on temperatures from 20ºC to 35ºC. Acid scarification of seeds with sulfuric acid was able of increasing significantly the percentage of seed germination.